Accelerating energy transition through battery energy storage systems deployment: a review on current status, potential and challenges in Malaysia - Mohd Razif, Amani Syafiqah; Ab Aziz, Nur Fadilah; Ab Kadir, Mohd Zainal Abidin; Kamil, Karmila (Elsevier, 2024)
This paper examines the present status and challenges associated with Battery Energy Storage Systems (BESS) as a promising solution for accelerating energy transition, improving grid stability and reducing the greenhouse gas emissions. Serving as a key facilitator, BESS aids in integrating and balancing variable renewable energy sources to maintain a stable energy supply by storing excess energy and releasing it as needed. While global BESS deployment is on the rise, it falls short of aligning with storage capacity projections for a net-zero scenario, necessitating heightened efforts. In Malaysia, BESS is recognized as vital for system stability, prompting the government’s plan to install 5 units of 100 MW BESS capacity by 2034. The establishment of grid codes and regulations is critical for the safe and reliable integration of BESS. Although specific guidelines for BESS grid integration are limited, certain sections from existing guidelines for Large Scale Solar (LSS) connections can be adapted. To enable widespread BESS implementation, challenges such as scalability, grid integration, and cost need to be addressed. Robust guidelines and regulations must be developed to successfully integrate BESS into the grid and pave the way for a sustainable energy future. The motivation behind this study is to assess the current state of research on BESS and its integration into power systems, identifying challenges and opportunities associated with this technology. Additionally, the paper aims to shed light on the role of grid codes in governing the connection and operation of BESS and other energy storage systems within the grid.